Geopolymer reinforced concrete beams made with and without sand - Anuradha, R.; Sreevidya, V.; Venkatasubramani, R. (Journal of Structural Engineering, 2025)
An investigation on the flexural behaviour of reinforced Geopolymer concrete (GPC) has been conducted. Two kinds of systems were considered in this study using 100% replacement of cement by ASTM class F Flyash and 100% replacement of sand by M-sand. The beams were made with Geopolymer concrete having compressive strength in the range of M20 - M35 by ambient curing. The experimental ultimate moment was found to be about 40- 60 % higher than the predicted ultimate moment. Due to high stiffness of reactive Geopolymer concrete, the actual deflections of the beams were found to be slightly low allowable values under service loads. The observed crack widths under service loads were within acceptable limits. It was found that GPC made with sand and M-Sand had better structural integrity. Hence, there is a high potential to produce GPC using sand and M-Sand.